Rasgos de la ontología fundamental (2017)
The aim of this paper is to present the main features of the fundamental ontology of Martin Heidegger. In the development of thought points radicalism in the ontological difference: the first corresponds to the phenomenological nature of science, that is, to the search of a strict science Husserl, the second corresponds to the results of research conducted by Heidegger ontological and presented in Being and Time. In other words, the radical lead to the search for the foundation of ontology and at the same time, the originating status of the question of being, however, it is not a feature of fundamental ontology, open to the first feature, the ontological difference: Dasein. Understood as those achievements in the theming of the question of being, i.e. the search for the general sense of being to be found in the body with ontic-ontological primacy.